Metal oxide surface charge mediated hemostasis - Ostomel, Todd A (Langmuir : the ACS journal of surfaces and colloids, 2007)
Blood coagulates faster upon contact with polar glasslike surfaces than on nonpolar plastic surfaces; this phenomenon is commonly termed the glass effect. However, the variable hemostatic response that we report here for contact-activated coagulation by different metal oxides, all of which are polar substrates, requires a refinement of this simple polarity model of how inorganic metal oxides activate the intrinsic pathway of blood coagulation. To our knowledge, the role of metal oxide surface charge as determined at the physiological pH and Ca2+ concentration of blood has not been previously investigated. We find that basic oxides with an isoelectric point above the pH of blood are anticoagulant while acidic oxides with an isoelectric point below the pH of blood are procoagulant. Using a thromboelastograph, we find that the onset time for coagulation and rate of coagulation post-initiation depend on both the sign and the magnitude of the initial surface charge density of the metal oxide. This work presents a useful strategy based on a quantifiable material parameter to select metal oxides to elicit a predictable and tunable biological response when they are in contact with blood